2013
DOI: 10.1155/2013/592371
|View full text |Cite
|
Sign up to set email alerts
|

Autism in the Faroe Islands: Diagnostic Stability from Childhood to Early Adult Life

Abstract: Childhood autism or autism spectrum disorder (ASD) has been regarded as one of the most stable diagnostic categories applied to young children with psychiatric/developmental disorders. The stability over time of a diagnosis of ASD is theoretically interesting and important for various diagnostic and clinical reasons. We studied the diagnostic stability of ASD from childhood to early adulthood in the Faroe Islands: a total school age population sample (8–17-year-olds) was screened and diagnostically assessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The studies that Helt and colleagues review have mainly assessed younger children and the fact that our results on adult males are within ranges shown on children adds support for our findings. Other studies on diagnostic stability of ASDs within normal range IQ have had shorter follow‐up times, usually between 1 and 7 years (according to Helt et al., ), and the few studies with longer follow‐up have had fewer cases with normal range IQ (e.g., Howlin & Moss, ; Howlin et al., ; Kocovska et al., ). Our results could therefore be considered to be fairly unique regarding long‐term follow‐up of diagnostic stability in males with AS with normal range IQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that Helt and colleagues review have mainly assessed younger children and the fact that our results on adult males are within ranges shown on children adds support for our findings. Other studies on diagnostic stability of ASDs within normal range IQ have had shorter follow‐up times, usually between 1 and 7 years (according to Helt et al., ), and the few studies with longer follow‐up have had fewer cases with normal range IQ (e.g., Howlin & Moss, ; Howlin et al., ; Kocovska et al., ). Our results could therefore be considered to be fairly unique regarding long‐term follow‐up of diagnostic stability in males with AS with normal range IQ.…”
Section: Discussionmentioning
confidence: 99%
“…There have been more studies made regarding stability of autistic disorder (AD) and PDD-Not Otherwise Specified (PDD-NOS). AD combined with intellectual disability has been shown to be stable in the long-term perspective but there is greater variability when intelligence is within normal range (Billstedt, Gillberg, & Gillberg, 2005;Howlin, Goode, Hutton, & Rutter, 2004;Howlin & Moss, 2012;Kocovska et al, 2013). A recent metaanalysis on the diagnostic stability of AD and PDD-NOS in children (3-10 years of age), reported that approximately 25% of subjects with PDD-NOS move off the autism spectrum when followed up after 1-7 years, compared to 9% of those with AD (Rondeau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we did not have access to a current diagnosis of ASD, and individuals classified as having ASD were required to have been clinically diagnosed with ASD at three or four of the previous examinations (the last follow-up being 12 years before the current study). This procedure is nevertheless justified since autistic traits are relatively stable (Helles, Gillberg, Gillberg, & Billstedt, 2015;Kocovska et al, 2013;Whitehouse, Hickey, & Ronald, 2011) and it is not known to which extent those, and especially women, who lose their clinical diagnosis do so because of learning strategies to compensate for their social and communication difficulties. Women are underdiagnosed and there is an unmet need for better characterization of symptomatology of female adults with ASD.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This procedure is nevertheless justified since autistic traits are relatively stable(Helles, Gillberg, Gillberg, & Billstedt, 2015;Kocovska et al, 2013;Whitehouse, Hickey, & Ronald, 2011) and it is not known to which extent those, and especially women, who lose their clinical diagnosis do so because of learning strategies to compensate for their social and communication difficulties. First, our sample size was small.…”
mentioning
confidence: 99%
“…We previously showed that the prevalence of autism in the Faroe Islands (0.94% of the population (7)(8)(9)) was similar to many other western countries. In this study, we ascertained the genetic profile of 357 individuals including an epidemiological cohort of 36 individuals with autism born between 1985 and 1994 (Fig 1 and S1 Fig), their relatives (n=136) and a group of 185 controls.…”
Section: Introductionmentioning
confidence: 67%